PENGARUH PERSEPSIAN GAYA KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL PADA PERILAKU KEWARGAAN ORGANISASIONAL YANG DIMEDIASI OLEH PEMBERDAYAAN PSIKOLOGIS DI PT TRIPATRA - , Leonardus Herwindo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research develops theoretical model to understand the occurrence of organizational citizenship behavior in the organization. The study that was conducted in Tripatra examined the impact of perceived transactional and transformational leadership towards organizational citizenship behavior mediated by psychological empowerment. The objectives of this study are to prove the results theoretically as well as to compare with the actual situation in the field, which is Tripatra organization to get better analysis for future improvement. Data was collected using purposive sampling (non random) from 264 Tripatraâs employees in Jakarta, both contract and permanent basis, from the total population of 1,095 employees. The minimum of 2 years of experience with Tripatra was used as criteria. The result analysis used hierarchical regression and regression with Baron and Kenny procedure (1986). The study found that independently, the perceived transactional dan transformational leadership has positive impact to the occurrence of organizational citizenship behavior. Surprisingly, the perceived transformational leadership explained no incremental variance in organizational citizenship behavior. The study suggests that the proper implementation of contingent reward and active management-by-exception may be perceived as distributive justice that triggers employees to perform extra-roles. Another finding of this study was the psychological empowerment has full mediating role in examining the relationship between perceived transformational leadership and organizational citizenship behavior.